Ethnic Variation in the Most Common Shade of Anterior Teeth among Malaysian Students: A Cross-sectional Study. - Ravi Gupta; Ishani Saluja (Universidad de Concepción., 2023)
Aim: Determination of the most common shade of anterior teeth in Malaysian students of different ethnicities. Materials and Methods: A total of 120 subjects, 40 each from different ethnicities (Malay, Chinese, and Indian) aged 18-22 years were evaluated for tooth shade using the VITA Classical shade guide. The subject was asked to sit in an up-right position with teeth at the clinician's eye level and the subject was instructed to remove makeup or tinted eyewear which may affect the result. The procedure was done in natural daylight. The shade tabs were positioned adjacent to the maxillary central incisor and the middle 1/3rd of the facial surface was assessed by experts to determine the correct tooth shade. The data was statistically analysed. Results: The differences in tooth shade were seen among the subjects of different ethnicities. The Malay ethnicity has B1 (37%) as the most common tooth shade whereas Chinese has C1 (27%) and Indian C1 (40%). Conclusions: Under the limitation of the study, it was found that there is a relationship between tooth color and ethnic background. Malay students tend to have brighter teeth as compared to Chinese and Indian students.